Flexible force sensors for e-textiles - Carvalho, Helder (2017)
This paper presents the development of inexpensive, lightweight, flexible polymer-based piezoresistive sensors appropriate for integration in e-textiles. The transducing element used is a volume-conductive carbon impregnated black polypropylene/polyethylene film with commercial names Velostat (from 3M) or Linqstat (from Caplinq). The objective is to investigate on the influence of different sensor constructions, varying film thicknesses, electrode materials and encapsulations on sensor performance. Furthermore, ways of integrating the sensors into textile products, as well as potential applications are also studied. In this paper, the behaviour of the sensors under different cyclic compression loads, applied at different speeds, is presented. Sensors using three different electrode materials are tested. The results show significant influence of sensor construction and electrode material on the static and dynamic performance of the devices.